Evaluierung der Erfolgsfaktoren des EFQM-Modells in der os̈terreichischen Ernaḧrungswirtschaft anhand des Analytischen Hierarchieprozesses - Oliver Meixner; Siegfried Poc̈htrager; Rainer Haas (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
– Numerous companies in the Austrian food industry have already been certified in accordance with the ISO 9000 standards. However, the introduction of a quality management system in a company alone does not guarantee continuous improvement as required by the standard ON̈ORM ISO 9001:2000. In order to be successful when introducing and maintaining a quality management system in a company, a number of important factors must be considered. These success factors are derived from the "European Foundation for Quality Management (EFQM) Model for Business Excellence". The purpose of the EFQM Model is to support the internal assessment of the quality management within a company, and it can be regarded as a motor for internal improvement. In particular, for companies planning to introduce a quality management system it is very useful since it tells them which factors have to be taken into account even before they introduce the system. Basically, the EFQM defines a specific weighting of the 9 success factors of the model. The aim of the study is to evaluate the pre-determined weighting of the EFQM success factors for the Austrian food industry.
Keywords: 330; Qualitätsmanagement; Erfolgsfaktor; Hierarchie; Modellierung; Ernährungsindustrie; Österreich